2017
DOI: 10.1515/pjvs-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of leptin on anterior pituitary cells LH secretory activity during early pregnancy in pig

Abstract: Leptin modulates reproductive activity but its potential influence on LH secretion from anterior pituitary (AP) cells during implantation period in pigs (days 14-16 of pregnancy) remained unexplored. This study focused on determination whether leptin affects basal and GnRH-induced LH secretion and intracellular accumulation and whether leptin receptor (OB-Rb) mRNA is expressed in the AP gland during implantation in pigs. Four individual AP glands were developed into separate primary cultures. 2x10 5 cells/ml w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…The present study, we found that leptin dose-dependently accelerated the release and mRNA expression of LH in luteal cells. The results are in accordance with the reports on pituitary cells, which demonstrated that leptin directly promoted gonadotropin release [62][63][64]. Results obtained from trophoblasts cells suggested that leptin stimulated hCG secretion [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…The present study, we found that leptin dose-dependently accelerated the release and mRNA expression of LH in luteal cells. The results are in accordance with the reports on pituitary cells, which demonstrated that leptin directly promoted gonadotropin release [62][63][64]. Results obtained from trophoblasts cells suggested that leptin stimulated hCG secretion [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…The pituitary (1 pituitary per tube) was cultured in 500 μL of medium in a humidified atmosphere with 95% air and 5% CO 2 for 24 h at 37°C. The pituitary was divided into four groups: (i) control group (CON), cultured only in media, (ii) GnRH group, cultured in the presence of GnRH agonist at a dose of 100 ng/mL [35], (iii) GnRH+AP group, cultured in the presence of GnRH agonist and APLN-13 at a dose of 1 μg/mL [36], and (iv) GnRH+ML group, cultured in the presence of GnRH agonist and APLN inhibitor ML221 at a dose of 50 µ m [37]. After 24 h, media was collected for ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Dalam sistem syaraf pusat, hipotalamus adalah target utama leptin yang akan berikatan dengan neuron Gonadotropin (GnRH) untuk menstimulasi pelepasan GnRH. Leptin yang dihasilkan oleh jaringan lemak adiposa akan berikatan dengan GnRH untuk menstimulasi produksi FSH dan LH di hipofisa anterior (Slawrys & Gajewska, 2017). Hormon FSH dan LH mengatur ovulasi dan folikulogenesis.…”
Section: Pendahuluanunclassified
“…Peningkatan konsentrasi leptin diasosiasikan dengan onset pubertas pada beberapa babi dara (Rybska et al, 2018) (Takle et al, 2017). Melalui mekanisme terpusat di otak bagian hipotalamus, hormon leptin ini berfungsi menghubungkan antara jaringan adiposa dan sistem reproduksi dalam menyediakan dan mengatur kebutuhan energi untuk reproduksi dan kehamilan (Slawrys & Gajewska, 2017); Lents et al, 2020). Hewan yang mengalami insufisiensi hormon leptin akan mengalami keterlambatan dewasa kelamin, infertilitas disertai potensi obesitas.…”
Section: Pendahuluanunclassified